The Contribution of Friday Bikers Community to the Dilemma of Busy Household and Active Church Participation - Yovendi Mali Koli; Lolong Ambrosius; Martinus Joko Lelono (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Since the Second Vatican Council, the Church has been concerned with the active participation of its members. However, work demands have made it increasingly difficult for the faithful to participate in Church activities. This study aims to find a pastoral style that can encourage active participation among the faithful despite their work demands. The research employed the Interpretative Phenomenological Analysis (IPA) and comparative method to study the Friday Bikers Community, a categorical community in Banteng Parish, Semarang Archdiocese. The study revealed that the Friday Bikers Community serves as a model for the church, effectively balancing the demands of work and active participation in ecclesial activities. The Friday Bikers Community integrates churching in a genuine way, focusing on communio, relationships, inner dispositions, and existential limitations of its members.